Dry preparation method of PbS quantum dot film and phototransistor with PbS quantum dot film and silicon forming heterojunction
The PbS quantum dot film was prepared in a mixed atmosphere of hydrogen and inert gas by dry preparation, which solved the problem of organic ligands affecting carrier transport in wet preparation, and achieved high-efficiency carrier transport and improved performance of optoelectronic devices.
Patent Information
- Application Number
- CN202510859102.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-06-25
AI Technical Summary
In the prior art, organic ligands affect carrier transport in the wet preparation method of PbS quantum dots, resulting in poor device performance and no PbS quantum dot film preparation method without surface ligand is seen.
Using the dry preparation method, in a mixed atmosphere of hydrogen and inert gas, a PbI2 uniform continuous film is used as the Pb source to react with the S source to form a PbS quantum dot film, avoiding the participation of surface ligands, and promoting the reaction between the Pb source and the S source through hydrogen to control the nucleation density and growth of the quantum dots.
The preparation of PbS quantum dot film without surface ligand is realized, the carrier transport efficiency is improved, and the responsiveness and specific detection rate of optoelectronic devices are improved.
Smart Images

Figure CN120364745A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of optoelectronic technology and photodetectors, and particularly to a method for preparing a PbS quantum dot thin film, and a phototransistor with a heterojunction formed by the PbS quantum dot thin film and silicon. Background Art
[0002] Quantum dots have unique optoelectronic properties and have a wide range of application values including luminescence, detection, sensing, etc. A photodetector is a core component for converting optical signals into electrical signals and plays a key role in various optical detection scenarios. It utilizes the photoelectric effect of special materials to accurately sense light of different intensities and frequencies. Photodetectors are widely used in fields such as environmental detection, security monitoring, imaging, and optical communication, and are an indispensable and important part of modern optoelectronic technology. Traditional photodetectors are gradually difficult to meet the development requirements in terms of sensitivity, response speed, etc. Against this background, the research and development of photodetectors based on new functional materials has become the focus.
[0003] PbS quantum dots (Pbs quantum dots or Pbs QDs) are a kind of zero-dimensional semiconductor nanomaterial composed of lead (Pb) and sulfur (S) elements, with significant quantum confinement effects and relatively large Bohr exciton radii, which endow it with unique optical and electrical properties. By precisely controlling the size of the quantum dots, its bandgap can be adjusted to achieve precise regulation of the absorption and emission spectra in the near-infrared band. These advantages make PbS quantum dots have obvious advantages in the field of near-infrared light detection. At the same time, PbS quantum dots have a high extinction coefficient and strong light absorption ability, which can effectively improve the photoelectric conversion efficiency. These characteristics make it show great application potential in the field of photodetectors.
[0004] In the field of the synthesis of PbS quantum dots, the commonly used method is the wet preparation method. The wet preparation method refers to a reaction carried out in solution. In the synthesis process of a specific solution system, that is, the reactants undergo a chemical reaction in a liquid solvent. To control the size of the quantum dots and prevent their aggregation in the solution, a key feature of this method is that organic molecules must be added. These organic molecules wrapped on the surface of the quantum dots are called surface ligands (ligands). Known surface ligands include tetrabutylammonium iodide (TBAI) and ethanedithiol [ACS Photonics (2020), 7(8), 1932 - 1941], mercaptopropionic acid [ACS Applied Materials&Interfaces(2018), 10(36), 30283 - 30295], picolinic acid, 2,6 - dipicolinic acid, salicylic acid, thiourea, and thiosemicarbazide [Chemistry of Materials (2011), 23(18), 4158 - 4169], etc. PbS then forms core - shell structures such as PbS - ligand, dumbbell structures, or other more complex structures with these organic compounds; such quantum dots are called colloidal quantum dots. However, this core - shell wrapping structure increases the van der Waals interaction distance at the interface between quantum dots. For applications in optoelectronic devices, the organic ligands on the surface of the quantum dots will seriously affect the transport properties of carriers, thus affecting the device performance and stability. The PbS quantum dot products prepared by the wet method necessarily contain surface ligands, and the colloidal chemical synthesis method is one of the commonly used means. On the other hand, for quantum dots used in optoelectronic device applications, it is expected that individual quantum dots can form a complete continuous film rather than separated quantum dots; in this way, compared with individual separated quantum dots, a continuous and complete quantum dot film can improve light absorption, contribute to the transport of carriers, and enhance the characteristics of optoelectronic devices.
[0005] In the prior art, there is no relevant research report on the preparation method of PbS quantum dot films in which hydrogen is involved in the preparation process and no surface ligands are contained. Summary of the Invention
[0006] In view of the problems existing in this field, especially the fundamental problem that the organic ligands in the chemical preparation method lead to hindered carrier transport and poor device performance, the present invention proposes a dry preparation method for PbS quantum dot films. The PbS quantum dots prepared by the present invention have no organic ligands on their surfaces, significantly improving the nucleation density, thereby realizing the controllable preparation of quantum dots with smaller size and more uniform distribution, and enabling efficient carrier transport.
[0007] Solution system A solution system refers to a synthetic process environment in which reactants undergo chemical reactions in a liquid solvent to form products. In the field of quantum dot preparation, this usually refers to the traditional colloidal chemical synthesis method. A key feature of this system is that in order to control the size of quantum dots and prevent their aggregation in a liquid medium, specific organic molecules must be added as surface ligands during the reaction. The preparation method proposed in this patent is carried out in a non-solution system, which is fundamentally different. Without surface ligands Without surface ligands is a core feature describing the PbS quantum dots prepared in this patent, indicating that the surface of the quantum dots is clean and not wrapped by organic molecules. This is in sharp contrast to the quantum dots prepared by traditional methods, which must rely on surface ligands - those organic molecules that wrap around the quantum dots to control size and prevent aggregation in the colloidal synthesis method. However, these surface ligands will form an insulating core-shell structure on the surface of the quantum dots, increasing the distance between the quantum dots, thus seriously hindering the effective transport of carriers and ultimately affecting the performance and stability of the device. Therefore, preparing quantum dots without surface ligands by the method of this patent eliminates this insulating barrier and promotes efficient carrier transport between quantum dots, significantly improving key performance such as the responsivity and specific detectivity of optoelectronic devices.
[0008] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a dry preparation method for PbS quantum dot films. The preparation method is to react a PbI2 uniform continuous film as a Pb source and an S source to form a PbS quantum dot film in a mixed atmosphere of hydrogen and an inert gas.
[0009] Completely different from the wet preparation method, the reaction system of the dry preparation method of the present invention neither involves surface ligands nor uses a solvent. The reaction system of the preparation method of the present invention is a reaction system without the participation of surface ligands.
[0010] Specifically, the reaction formula of the reaction involved in the preparation method of the present invention is as follows: The reaction described in the present invention is a free radical reaction process, and its principle schematic diagram is as follows: Among them, the use of H2 is crucial for improving the synthesis efficiency of PbS. In a pure inert gas such as argon or nitrogen system, the decomposition of PbI2 mainly depends on thermodynamic driving. Due to the relatively high chemical bond energy of PbI2 (the bond energy of the Pb-I bond is about 200 kJ / mol), it is difficult to efficiently release Pb atoms only through thermal activation. Only local fracture may occur on the surface of PbI2, resulting in a limited number of released Pb atoms and poor dispersion. This inefficient decomposition directly limits the nucleation site density of quantum dots, forcing the limited Pb atoms to aggregate through surface diffusion to form large-sized particles, and it is difficult to obtain quantum dots with quantum effects. After the intervention of H2, the decomposition path is changed through functional reactions. H2 can accelerate the decomposition of PbI2 to generate Pb-containing free radicals and volatile HI. At the same time, H2 reacts with I2 (directly generated by the reaction of PbI2 and S) to generate HI, reducing the concentration of I2 in the gas phase, promoting the direct reaction of PbI2 and S, and also promoting the continuous decomposition of PbI2 to release more Pb to participate in the reaction. The function of H2 helps to increase the generation rate of Pb atoms, thereby forming a large number of uniformly distributed Pb atom clusters on the substrate surface, providing dense nucleation sites for subsequent sulfide reactions and finally forming a quantum dot film. In this way, appropriate hydrogen accelerates the decomposition of PbI2, significantly increasing the local concentration of Pb atoms in the reaction system, reducing the critical free energy required for nucleation, and resulting in a significant increase in nucleation density. At the same time, the high-density initial nucleation sites will quickly consume the Pb atoms in the system, inhibiting subsequent secondary nucleation, thereby forming quantum dots with uniform sizes. In a pure inert gas such as argon or nitrogen system, due to the low nucleation density, the Pb atoms that do not participate in nucleation have a high surface mobility and tend to combine with existing quantum dots through diffusion, resulting in the continuous growth of large particles by "swallowing" small particles and finally forming a coarsened structure with a relatively large radius.
[0011] Furthermore, the preparation method satisfies at least one of the following characteristics: 1) In the mixed atmosphere of hydrogen and inert gas, the ratio of hydrogen to inert gas is 2:1 to 2:5.
[0012] 2) The uniform and continuous PbI2 thin film is prepared on the substrate by a physical vapor deposition method (such as thermal evaporation), and the thickness of the PbI2 thin film on the substrate does not exceed 5 nm. Preferably, the thickness of the PbI2 thin film on the substrate is 1 - 5 nm; more preferably, the thickness of the PbI2 thin film on the substrate is 1 - 2 nm.
[0013] 3) The S source described above is solid sulfur powder or H2S. Among them, the solid S source is sulfur powder, which is heated to form gaseous sulfur; H2S, as a gaseous S source, is more uniform and has higher reaction activity than solid sulfur.
[0014] Among them, sulfur powder generates gaseous S8 ring molecules at high temperature, but the chemical reaction with Pb needs to overcome a relatively high energy barrier. In a pure inert gas system such as argon or nitrogen, the reaction rate between sulfur vapor and Pb is limited by the activation degree of sulfur, resulting in a slow and non-uniform reaction process. "Starvation growth" occurs in some areas due to insufficient sulfur supply. The introduction of hydrogen optimizes the activation process of sulfur through sulfur chain breakage catalysis (H2 can react with S8 molecules to generate HS· free radicals, such as S8 + H2 → 2HS4·, reducing the energy required for sulfur chain breakage and promoting sulfur to participate in the reaction in a more active small molecule form (such as S2, S4)) and surface reaction acceleration (HI generated by the reaction of H2 and PbI2 can act as an acidic medium, enhancing the adsorption ability of sulfur vapor on the Pb surface, enabling sulfur atoms to cover the Pb cluster surface more uniformly and forming a dense PbS lattice). The inert gas mainly plays a role in physical mass transfer and thermal equilibrium; while hydrogen becomes the dominant factor in the reaction through its chemical activity and kinetic regulation. Therefore, hydrogen plays multiple roles in the preparation of PbS quantum dots: its chemical activity directly promotes the decomposition of precursors, kinetic regulation inhibits crystal coarsening, and at the same time optimizes the activation of sulfur and surface reactions. In contrast, due to the lack of chemically active components in a pure inert system, the reaction is limited by thermodynamic equilibrium, resulting in a low nucleation density and uncontrollable growth.
[0015] Furthermore, the temperature condition of the reaction is 220~300 °C.
[0016] The present invention also provides a PbS quantum dot thin film, which is obtained by the aforementioned method, and the coverage rate of PbS quantum dots on the substrate surface is not less than 50% of the thin film. The surface of the bS quantum dots prepared by the present invention does not contain surface ligands.
[0017] Preferably, the substrate is selected from insulating materials or semiconductor materials, including one or a combination of two or more of glass, SiO2, SiC, Si3N4, Al2O3, sapphire, mica, MgO, Si, two-dimensional materials such as MoS2, etc.
[0018] The present invention also provides a heterojunction phototransistor formed by a PbS quantum dot thin film and silicon, and its characteristics include: the heterojunction phototransistor is composed of a silicon layer and the PbS quantum dot thin film prepared by the above method.
[0019] Preferably, a PbS quantum dot thin film forms a heterojunction phototransistor with silicon, which is characterized in that there is a two-dimensional layered material layer between the silicon layer and the PbS quantum dot thin film, and the layered material thin film includes one or more combinations of graphene, transition metal chalcogenides such as MoS2, PtSe2, CrS2, etc.
[0020] Preferably, a PbS quantum dot thin film forms a heterojunction phototransistor with silicon, which is characterized in that there is an insulating layer between the silicon layer and the PbS quantum dot thin film, and the insulating layer material includes SiO2 and high dielectric constant HfO2, Hf (1-x) ZrxO2 (HZO), Al2O3, TiO2, ZrO2, Ta2O5 and Bi2SeO5; the thickness of the insulating layer is 2 - 20 nm.
[0021] More preferably, a PbS quantum dot thin film forms a heterojunction phototransistor with silicon, which is characterized in that there is a two-dimensional layered material layer between the insulating layer and the PbS quantum dot thin film, and the layered material thin film includes one or more combinations of graphene and transition metal chalcogenides.
[0022] Compared with the prior art, the advantages of the present invention are as follows: In the present invention, a PbI2 thin film is used as a Pb source, and hydrogen participates in the reaction to promote the reaction between the Pb source and the S source to be converted into PbS quantum dots, and the density of the grown PbS quantum dots can be regulated to form a PbS quantum dot thin film. The method for preparing the PbS quantum dot thin film in the present invention is simple, and the surface of the prepared quantum dots does not contain an organic ligand layer, which is easy to control the preparation of PbS quantum dots and the coverage rate on the substrate surface, improving the preparation efficiency and material quality; it is helpful for the application in the preparation of high-performance optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the method for preparing the PbS quantum dot thin film of the present invention; Figure 2 It is a scanning electron microscope image of the PbS quantum dot thin film prepared in Example 2; Figure 3 It is an X-ray photoelectron spectrometer of the PbS quantum dot thin film prepared in Example 2; Figure 4 It is a scanning electron microscope image of the PbS quantum dot thin film prepared in Example 3; Figure 5 It is a scanning electron microscope image of the PbS quantum dot thin film prepared in Example 4; Figure 6 It is a scanning electron microscope image of the PbS quantum dot thin film prepared in Example 5; Figure 7X-ray photoelectron spectrometer of the PbS quantum dot film prepared in Example 5; Figure 8 Scanning electron microscope image of the PbS quantum dot film prepared in Comparative Example 1; Figure 9 For Example 3( Figure 9 b) and Comparative Example 1( Figure 9 a) Size statistical analysis of the prepared PbS quantum dots; Figure 10 Result of Example 7, that is, the current-voltage relationship of the photodetector constructed with the PbS quantum dot films prepared in Example 2 (device 2), Example 3 (device 3) and Comparative Example 1 (device 1). Different color curves in the legend represent different incident light intensities (mW cm -2 ); Figure 11 Result of Example 8, that is, the current-voltage relationship of the photodetector constructed with PbS (quantum dot film) / MoS2 / SiO2(20 nm) / Si. Different color curves in the legend represent different incident light intensities (mW cm -2 ); Figure 12 Scanning electron microscope image of the PbS colloidal quantum dots used in Comparative Example 2.
[0024] Figure 13 X-ray photoelectron spectrometer characterization results of the PbS quantum dots prepared in Comparative Example 3, (a) S 2p , (b) Pb 4f and (c) I 3d spectra.
[0025] Figure 14 Scanning electron microscope image of the PbS quantum dots prepared in Comparative Example 2 Detailed implementation mode Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0026] Example 1 A dry preparation method of a PbS quantum dot film of the present invention, the reactants include PbI2, S and H2, and the preparation method includes the following steps (for the schematic diagram, see Figure 1 ): 1) React PbI2 uniform continuous film as the Pb source with the S source to form PbS quantum dots in an inert gas atmosphere; 2) In the above step 1), hydrogen participates in the reaction; 3) In the above step 1), the reaction temperature is 220 – 300 °C; 4) The ratio of hydrogen to inert gas is 2∶1 ~ 2∶5; 5) The PbS quantum dot film mentioned refers to a film with a coverage rate of PbS quantum dots on the substrate surface not less than 50%, and the coverage rate result is obtained by calculating the particles in the SEM image.
[0027] The preparation method of the PbS quantum dot film of the present invention does not involve surface ligands and does not use solvents.
[0028] The reaction formula of the reaction mentioned is as follows: The PbI2 film is prepared on the substrate by thermal evaporation, with a thickness not exceeding 5 nm. The thickness within this range has no obvious difference on the subsequent formation of the PbS quantum dot film. The substrate is selected from insulating materials or semiconductor materials, including one or a combination of two or more of glass, SiO2, SiC, Si3N4, Al2O3, sapphire, mica, MgO, Si, two-dimensional materials such as MoS2, etc.
[0029] The S source can be solid sulfur powder or H2S. The solid sulfur powder can be heat-treated to form gaseous sulfur; its basic chemical conversion process is: solid sulfur (S) evaporates into S8 at high temperature, and H2 reacts with S to generate highly reactive HS• radicals, etc. As a gaseous S source, H2S is more uniform and has higher reactivity than solid S.
[0030] When the chemical reaction proceeds, the substrate is heated at a constant rate and then held at a constant temperature, and the constant temperature is 220 - 300 °C.
[0031] Example 2 It has the implementation content of the above example. For the specific implementation manners of the above example, reference can be made to the above description, and the examples here will not be repeated in detail; in Example 2, the difference from the above example is: In this example, first, a 10 mm×10 mm silicon wafer is successively cleaned with acetone / isopropanol / ethanol / deionized water and dried with dry nitrogen for standby. A 2 nm thick PbI2 film is deposited on the above substrate as the Pb source at a rate of 0.02 nm / s by thermal evaporation coating, and then sent into the CVD (chemical vapor deposition) system and placed at the downstream end of the carrier gas. 300 mg of sulfur powder is weighed and loaded into a quartz boat, which is then sent into the CVD system and placed at the upstream end of the carrier gas. The system is evacuated with a mechanical pump to make the background vacuum of the system lower than 1.0 × 10 -1 Pa.
[0032] The participation of hydrogen is by introducing a mixed gas of a certain flow rate of H2 (20 sccm) and Ar (10 sccm). After the gas flow is stable, the CVD system starts to heat up. The heating rate is 25 °C / min. When the system temperature is heated to 250 °C, it is maintained for 100 min until the reaction ends.
[0033] After the reaction ends, let the CVD system cool down slowly to 170 °C. During this period, increase the gas flow rate of the inert gas, and then quickly cool the system to room temperature to obtain a denser quantum dot film. The obtained quantum dot film is characterized by scanning electron microscopy ( Figure 2 ), and it can be seen that a relatively uniform quantum dot structure is formed. The prepared quantum dot film is characterized by X-ray photoelectron spectroscopy (XPS). The XPS characterization verifies that the formed quantum dot sample is PbS quantum dots ( Figure 3 ).
[0034] Example 3 It has the implementation content of the above example. For the specific implementation manners of the above example, reference can be made to the above description, and the examples here will not be repeated in detail; in Example 3, the difference from the above example is that: In this example, first, a 10 mm×10 mm silicon wafer is cleaned successively with acetone / isopropanol / ethanol / deionized water, and dried with dry nitrogen for standby. A 1 nm thick PbI2 film is deposited on the above substrate at a rate of 0.02 nm / s by thermal evaporation coating as a Pb source, and is sent into the CVD system and placed at the downstream end of the carrier gas. Weigh 300 mg of sulfur powder and load it into a quartz boat, and send it into the CVD system and place it at the upstream end of the carrier gas. Use a mechanical pump to evacuate the vacuum so that the background vacuum of the system is lower than 1.0 × 10 -1 Pa.
[0035] Introduce the H2 / Ar mixed gas, where the flow rate of H2 is 20 sccm and the flow rate of Ar is 20 sccm. After the gas flow is stable, the CVD system starts to heat up. The heating rate is 25 °C / min. When the system temperature is heated to a certain temperature of 300 °C, it is maintained for 100 min until the reaction ends.
[0036] After the reaction ends, let the CVD system cool down slowly to 170 °C. During this period, increase the gas flow rate of the inert gas, and then quickly cool the system to room temperature to obtain a dense quantum dot film. The prepared quantum dot film is characterized by XPS, and its XPS results are the same as the above Figure 3 ones. The obtained PbS quantum dot film is characterized by scanning electron microscopy ( Figure 4 ), and PbS quantum dots with relatively uniform sizes are obtained. Compared with Example 2, it can be seen from the SEM that the density of PbS quantum dots in the quantum dot film prepared in Example 3 is higher than that in Example 2.
[0037] Example 4 It has the implementation content of the above embodiments. For the specific implementation manners of the above embodiments, reference can be made to the above description, and the embodiments here will not be repeated in detail; in Example 4, the difference from the above embodiments is that: In this embodiment, first, a silicon wafer of 10 mm×10 mm is successively cleaned with acetone / isopropanol / ethanol / deionized water, and dried with dry nitrogen for standby. Using thermal evaporation coating, a PbI2 thin film (5 nm) with a certain thickness is deposited on the above substrate at a rate of 0.02 nm / s as the Pb source, and it is sent into the CVD system and placed at the downstream end of the carrier gas. H2S is selected as the S source. Using a mechanical pump to evacuate, so that the background vacuum of the system is lower than 1.0 × 10 -1 Pa.
[0038] A mixed gas of H2 / Ar is introduced, where the flow rate of H2 is 20 sccm and the flow rate of Ar is 30 sccm. After the gas flow is stable, the CVD system starts to heat up. The heating rate is 25 °C / min. When the system temperature is heated to 220 °C, it is maintained for 100 min until the reaction ends. After the reaction ends, let the CVD system cool down slowly to 170 °C. During this period, increase the gas flow rate of the inert gas, and then quickly cool the system to room temperature to obtain a dense PbS quantum dot thin film (as Figure 5 shown).
[0039] Example 5 It has the implementation content of the above embodiments. For the specific implementation manners of the above embodiments, reference can be made to the above description, and the embodiments here will not be repeated in detail; in Example 5, the difference from the above embodiments is that: In this embodiment, MoS2 / SiO2(20 nm) / Si is used as the substrate, and a PbS quantum dot thin film is prepared on the surface of two-dimensional MoS2. Using thermal evaporation coating, a 2-nm-thick PbI2 thin film is deposited on the above substrate at a rate of 0.02 nm / s as the Pb source, and it is sent into the CVD system and placed at the downstream end of the carrier gas. Weigh 300 mg of sulfur powder and load it into a quartz boat, and send it into the CVD system and place it at the upstream end of the carrier gas. Using a mechanical pump to evacuate, so that the background vacuum of the system is lower than 1.0 × 10 -1 Pa.
[0040] Introduce a H2 / Ar mixed gas, where the flow rate of H2 is 20 sccm and the flow rate of Ar is 50 sccm. After the gas flow stabilizes, the CVD system starts to heat up. The heating rate is 25 °C / min. When the system temperature reaches 250 °C, maintain it for 100 min until the reaction ends. After the reaction ends, let the CVD system cool down slowly to 170 °C. During this period, increase the flow rate of the inert gas, and then quickly cool the system to room temperature to obtain a dense PbS quantum dot film ( Figure 6 and Figure 7 ).
[0041] Comparative Example 1 In this example, compared with Example 2, hydrogen was not used during the reaction in Comparative Example 1. In this example, first, a 10 mm × 10 mm silicon wafer was cleaned successively with acetone / isopropanol / ethanol / deionized water and dried with dry nitrogen for standby. A 2 nm thick PbI2 film was deposited on the above substrate at a rate of 0.02 nm / s by thermal evaporation coating as a Pb source, which was sent into the CVD system and placed at the downstream end of the carrier gas. Weigh 300 mg of sulfur powder and put it into a quartz boat, which was sent into the CVD system and placed at the upstream end of the carrier gas. Use a mechanical pump to evacuate the system to make the background vacuum of the system lower than 1.0 × 10 -1 Pa.
[0042] The flow rate of the inert gas Ar introduced is 20 sccm. After the gas flow stabilizes, the CVD system starts to heat up. The heating rate is 25 °C / min. When the system temperature reaches 250 °C, maintain it for 100 min until the reaction ends.
[0043] After the reaction ends, let the CVD system cool down slowly to 170 °C. During this period, increase the flow rate of the inert gas, and then quickly cool the system to room temperature to obtain sparse quantum dots. The prepared quantum dots were characterized by XPS, and its XPS results are the same as the above Figure 3 , indicating that PbS quantum dots were obtained. The obtained PbS quantum dots were characterized by scanning electron microscopy. As Figure 8 shown, the density of PbS quantum dots prepared under CVD conditions without H2 (compared with those using H2) decreased by about 20 times.
[0044] Furthermore, by analyzing the size distribution of the PbS quantum dots prepared in Example 3 and Comparative Example 1 ( Figure 9 ), in the system of Ar inert atmosphere, the density of PbS quantum dots is about 13 per μm 2 , and the radius of the quantum dots is concentrated between 40 - 60 nm ( Figure 9 a); while after introducing H2 (the ratio of H2 to Ar is 1:1), the density of the quantum dots increased significantly to about 261 per μm 2 , and at the same time, the size was concentrated and greatly reduced to a radius of 10 - 20 nm (Figure 9 b); smaller and more uniform in size. This significant difference stems from the synergistic regulation of hydrogen on reaction kinetics, nucleation processes, and crystal growth mechanisms.
[0045] Example 6 The present invention also discloses a heterojunction phototransistor formed by a PbS quantum dot thin film and silicon, comprising a silicon layer and the PbS quantum dot thin film prepared by the present invention.
[0046] Optionally, a heterojunction phototransistor formed by a PbS quantum dot thin film and silicon is characterized in that an insulating layer is provided between the silicon layer and the PbS quantum dot thin film, and the insulating layer material includes SiO2 and high dielectric constant HfO2, Hf (1-x) Zr x O2 (HZO), Al2O3, TiO2, ZrO2, Ta2O5, and Bi2SeO5; the thickness of the insulating layer is 2 - 20 nm.
[0047] Optionally, a heterojunction phototransistor formed by a PbS quantum dot thin film and silicon is characterized in that there is a two-dimensional layered material layer between the silicon layer and the PbS quantum dot thin film, and the layered material thin film includes one or more combinations of graphene, transition metal chalcogenides such as MoS2, PtSe2, CrS2, etc.
[0048] Example 7 Based on the prepared PbS quantum dot thin films with different coverages, heterojunction phototransistors (hereinafter referred to as photodetectors) were fabricated. The device structure is PbS quantum dot thin film / SiO2 (5 nm) / Si. In this example, the PbS quantum dot thin films of Comparative Example 1, Example 2, and Example 3 were used, and Au (30 nm) / Cr (5 nm) was used as the electrodes (source and drain electrodes) in contact with the PbS quantum dot thin film to fabricate photodetectors, corresponding to device 1, device 2, and device 3 respectively. Different incident light intensities (0.8 mW / cm 2 、1.8 mW / cm 2 、3.2 mW / cm 2 and 5.6 mW / cm 2 ) in the 1550 nm band and a source-drain bias voltage V ds = 1 V were used for testing. As Figure 10 shown, under the same test conditions, the current of the PbS quantum dot device prepared by Comparative Example 1 (device 1) is the smallest; from this, the corresponding responsivity (R) and specific detectivity (D) of the photodetector can be calculated. For example, at an incident light intensity of 0.8 mW cm -2 in the 1550 nm band and a source-drain bias voltage V dsWhen the voltage is 1 V, the responsivity and specific detectivity of device 1 are 1.07 A / W and 6.1×10 10 Jones, respectively, while those of device 2 are 54 A / W and 4.56×10 11 Jones, respectively, and those of device 3 are 95.1 A / W and 6.39×10 11 Jones. The results show that the performance of the photodetector improves with the increase of the PbS quantum dot density.
[0049] Example 8 In this example, the PbS quantum dot film is prepared by using the technical method of the above Example 5, that is, the PbS quantum dot film is prepared on the MoS2 / SiO2(20nm) / Si substrate, and then the heterojunction phototransistor is prepared by using Au(30 nm) / Cr(5 nm) as the electrodes (source and drain electrodes) in contact with the PbS quantum dot film. Figure 11 This is the current-voltage curve of the photodetector prepared in this example. The test conditions are as follows: different incident light intensities (0.8 mW / cm 2 、1.8 mW / cm 2 、3.2 mW / cm 2 and 5.6 mW / cm 2 ) in the 1550 nm band, and the source-drain bias voltage V ds = 1 V (no gate voltage is applied). Thus, the responsivity (R) and specific detectivity (D) of the photodetector under different light intensities can be calculated. For example, when the incident light intensity in the 1550 nm band is 0.8 mW cm -2 , the responsivity and specific detectivity are 93.4 A / W and 5.49×10 11 Jones, respectively.
[0050] Comparative Example 2 Compared with the PbS quantum dots (without organic ligand coating) of the present invention, PbS colloidal quantum dots (i.e., the surface of PbS quantum dots is coated with organic ligands, purchased from Suzhou Xingshuo Nano Technology Co., Ltd.) are used in Comparative Example 2 to construct a photodetector (colloidal-PbS / SiO2 / Si). Under the same test conditions as in Example 7, when the incident light intensity in the 1550 nm band is 0.8 mW cm -2 and the bias voltage V ds = 1 V, the responsivity of the photodetector in Comparative Example 2 is about 16.25 A / W, and the specific detectivity is 1.35×10 11Jones; this performance is significantly lower than that of device 2 and device 3 in Example 7 (i.e., PbS quantum dot devices without organic ligands when the PbS density is relatively large). Therefore, the performance of the photodetector with the PbS quantum dot thin film without organic ligands prepared by the present invention is superior to that of the devices with PbS quantum dots with ligands. Figure 12 SEM image (5 µm × 5 µm) of PbS quantum dots with ligands.
[0051] Comparative Example 3 In this example, compared with Example 2, PbI2 with a thickness greater than 5 nm was used as the Pb source in Comparative Example 3.
[0052] In this comparative example, first, a 10 mm × 10 mm silicon wafer was successively cleaned with acetone / isopropanol / ethanol / deionized water, and dried with dry nitrogen for standby. A 6-nm-thick PbI2 thin film was deposited on the above substrate at a rate of 0.02 nm / s by thermal evaporation coating as the Pb source, and then sent into the CVD (chemical vapor deposition) system and placed at the downstream end of the carrier gas. 300 mg of sulfur powder was weighed and loaded into a quartz boat, and then sent into the CVD system and placed at the upstream end of the carrier gas. The system was evacuated with a mechanical pump to make the background vacuum of the system lower than 1.0 × 10 -1 Pa.
[0053] The participation of hydrogen was to introduce a mixed gas of a certain flow rate of H2 (20 sccm) and Ar (10 sccm). After the gas flow was stable, the CVD system began to heat up. The heating rate was 25 °C / min. When the system temperature was heated to 250 °C, it was maintained for 100 min until the reaction ended.
[0054] After the reaction ended, the CVD system was slowly cooled to 170 °C. During this period, the gas flow rate of the inert gas was increased, and then the system was quickly cooled to room temperature. The obtained material was characterized by X-ray photoelectron spectroscopy (XPS). The XPS characterization verified that both PbS and unreacted PbI2 existed in the obtained material ( Figure 13 ). The obtained sample was characterized by scanning electron microscopy ( Figure 14 ), and it can be seen that in addition to quantum dots, there are also nanowire-like substances and thin film-like substances. Therefore, when a PbI2 thin film with a thickness greater than 5 nm is used as the Pb precursor, it is difficult to completely convert it into PbS quantum dots.
[0055] The performance parameters for characterizing photodetectors also include response time, response at different wavelengths, etc., which can be referred to relevant literature Science China Materials 66, 193 (2023); Adv. Opt. Mater.【11,2300910 (2023)】, which will not be elaborated here. However, the photodetector based on the PbS quantum dot film prepared by the present invention has a wide spectral response characteristic in the ultraviolet to near-infrared wavelength range. On the one hand, this is due to the fact that the prepared PbS quantum dots have different sizes (band gaps) as shown in Figure 9 , and on the other hand, it is determined by the device structure of the heterojunction formed by the PbS quantum dot film and silicon.
[0056] As mentioned above, the above are only the preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, making equivalent substitutions or changes, shall be covered by the protection scope of the present invention.
Claims
1. A dry preparation method of a PbS quantum dot thin film, characterized in that, The preparation method is to react a PbI2 uniform continuous film as a Pb source and an S source in a mixed atmosphere of hydrogen and an inert gas to form a PbS quantum dot film.
2. The preparation method according to claim 1, characterized in that, The preparation method satisfies at least one of the following characteristics: 1) In the mixed atmosphere of hydrogen and an inert gas, the ratio of hydrogen to the inert gas is 2:1 to 2:5; 2) The PbI2 uniform continuous film is prepared on a substrate by physical vapor deposition, and the thickness of the PbI2 film on the substrate does not exceed 5 nm; 3) The S source is solid sulfur powder or H2S, and the solid S source is sulfur powder, which is heated to form gaseous sulfur.
3. The preparation method according to claim 2, characterized in that, The temperature condition of the reaction is 220 - 300 °C.
4. A PbS quantum dot thin film, characterized in that, Prepared by the method according to any one of claims 1 - 3.
5. The PbS quantum dot thin film according to claim 4, characterized in that, The PbS quantum dot film has the following characteristics: the coverage rate of PbS quantum dots in the PbS quantum dot film on the substrate surface is not less than 50%.
6. The PbS quantum dot thin film according to claim 4, wherein The substrate is selected from insulating materials or semiconductor materials, including one or a combination of two or more of glass, SiO2, SiC, Si3N4, Al2O3, sapphire, mica, MgO, Si, two-dimensional materials such as MoS2, etc.
7. A PbS quantum dot thin film forms a heterojunction phototransistor with silicon, and its characteristics include: The heterojunction phototransistor is composed of a silicon layer and the PbS quantum dot film according to claim 4.
8. The PbS quantum dot thin film and silicon heterojunction phototransistor according to claim 7, characterized in that it includes, An insulating layer is provided between the silicon layer and the PbS quantum dot film, where: The insulating layer material described includes SiO2 and high dielectric constant HfO2, Hf (1-x) Zr x O2 (HZO), Al2O3, TiO2, ZrO2, Ta2O5, and Bi2SeO5; The thickness of the insulating layer is 2 - 20 nm.
9. The PbS quantum dot thin film and silicon heterojunction phototransistor according to claim 7, characterized by including, A two-dimensional layered material layer is provided between the silicon layer and the PbS quantum dot film, and the layered material film includes one or a combination of graphene and transition metal chalcogenides.
10. A PbS quantum dot thin film and silicon heterojunction phototransistor according to claim 8, characterized in that, A two-dimensional layered material layer is provided between the insulating layer and the PbS quantum dot film, and the layered material film includes one or a combination of graphene and transition metal chalcogenides.
Citation Information
Patent Citations
Method for fabrication of layered heterojunction polymeric devices
CN102414260A
Solar fluorescence aggregator based on PbS quantum dots matched with antireflection film and preparing method thereof
CN106558627A
Preparation method of low-energy-consumption graphene film
CN111847431A
Near-infrared photoelectric detector based on lead sulfide quantum dots and preparation method thereof
CN115810681A
Heterojunction structure based on PbS quantum dots and 1T-CrS2, preparation method thereof and photoelectric detector
CN117878171A